HIV-1 Genomic Surveillance Pipeline in Nigeria - F N MacDickson Celt (My University, 2024)
This review examines the proposed project to establish a comprehensive pipeline for ethical collection, next-generation sequencing, and analysis of HIV-1 genomic data across diverse patient populations in Nigeria. As antiretroviral therapy (ART) scales up in sub-Saharan Africa, the dual pressures of drug resistance emergence and substantial viral subtype variation pose significant public health risks. High-throughput sequencing (HTS) can elucidate viral evolution, detect resistance mutations early, and inform targeted interventions. By critically assessing the project’s rationale, objectives, methodology, expected outcomes, partnerships, and funding strategy, this review aims to highlight strengths, identify potential gaps, and offer recommendations that can optimize implementation and long-term impact.